Effective Combination of Advancing Transplantation Date with High-Yielding Cultivars for Paddy Rice Could Increase the Yield Potential Under Climate Warming in China - He Zhang; Guangsheng Zhou; Qijin He (Agronomy)
Climate change will have a significant impact on agricultural productivity. Rice is one of the main grains in the world, the stability of its production and supply is directly related to global food security. Based on field observation data from 2000 to 2012 and a biophysical process-oriented CERES-Rice crop model at three typical sites, we investigated the effects of cultivar improvement, different transplanting dates and their interactions on rice yield potential in the major paddy rice production areas of China. Rice planting systems were optimized with an optimal combination of varieties and transplanting dates, and their adaptability under future climate conditions (climate projections from five global climate models under four typical concentration path scenarios) was assessed. The results showed that cultivar improvement could increase the rice yield potential by 18.0–41.4%. The appropriate transplanting date might increase the yield potential of the existing rice by 1.9–6.7%. The advance in the transplanting date combined with the application of high-yielding cultivars would prolong the growth period of rice and increase the rice yield potential by 26.3–51.8%. An effective combination of the transplanting date and cultivar is an efficient approach to increase the yield potential of rice. The results provided an important reference and choice for the scientific management of and yield increase in rice in China.